A Case Study on The Role of Sociocultural Factors In ESL Pre-Service Teachers’ Beliefs And Practice - Wan Noor Miza Wan Mohd Yunus (JEELS (Journal of English Education and Linguistics Studies), 2020)
Pre-service teachers are often involved in the continuous construction and reconstruction of their identities that are shaped by various internal and external factors. This study explores sociocultural factors that influence pre-service teachers' beliefs about teaching and learning namely 1) previous schooling experience, 2) teacher education, and 3) curriculum specifications. Participants of the study were three pre-service teachers studying at a local university in Malaysia. Data were collected through face-to-face interviews conducted after their teaching practicum at local government schools. Findings from this study indicate that the three sociocultural factors have a varying degree of influence towards the pre-service teachers’ pedagogical beliefs and practice. Previous schooling experience and teacher education programme have the most influence on all the pre-service teachers' beliefs and practice while curriculum specifications have the least impact. It is also evident from this study that the formation of teachers' beliefs is complex as sociocultural factors such as ethnicity, gender, school and home are always interactional. The findings provide implications for ESL teacher educators in considering pre-service teachers' beliefs in teacher education programmes as these may significantly impact their pedagogical practices.